Análise aerodinâmica de asas através da teoria da linha sustentadora e do método da malha de vórtices - Cassol, Nádila Regina (Universidade Federal Rural do Semi-Árido, 2019)
The technological advancement of recent years has allowed high-performance projects in the aeronautics industry to be carried out with high accuracy in relatively short time. This work presents the comparative study of two numerical methods for aerodynamic analysis of a rectangular wing destined for the SAE Brazil AeroDesign competition and a trapezoidal wing, being they the Lifting Line Theory and the Vortex Lattice Method. The trapezoidal wing results will be compared to a NACA technical report, with wind tunnel experimental results. In this way, we can verify their reliability in order to point out the best method for designing unmanned radio-controlled aircraft, taking into account costs, time and accuracy of data. The present study concluded that the Vortex Lattice Method is closer to the values obtained in the experimental tests compared to the Lifting Line Theory in the wings of this study. As the wing length increased, the Lifting Line Theory began to approach more of the actual values, but still with lower results than the Vortex Lattice Method.
Monografia
Keywords: Aerodinâmica; Linha Sustentadora; Malha de Vórtices; Asas; Aerodynamics; Lifting Line Theory; Vortex Lattice Method; Wings; ENGENHARIAS::ENGENHARIA MECANICA